Static Culture of Spirulina platensis In Modified Sago Effluent Medium - Nurul Hana Minarti, Omar (Universiti Malaysia Sarawak, UNIMAS, 2010)
Effluent from Sago Mill is a polluting wastewater from the starch industries in Sarawak. The pollution occurs due to the large quantity produced daily rather the chemical components of the effluent. It is reported that for one kilogram (dry weight) of starch produced, 20 L of wastewater is generated in the process. This wastewater needs to be treated before to be discharged into nearby rivers. Therefore, in this study we proposed to use this wastewater as a media for the cultivation of the alga Spirulina platensis with the aim to make more attractive its production from an economical point of view by decreasing the production cost. Spirulina platensis has commercial importance due to overall nutritional qualities, especially high protein (70% dry basis) and vitamin contents, particularly B12. To use the sago effluent as the media for the growing of Spirulina, it needs to be modified. To produce modified sago effluent (MSE), the sago effluent was pre-treated aerobically by the addition of the commercial microbial consortium Bakwira MP300 with the aim to degrade the remained organic materials. Upon cleaned-up the MSE was amended with sodium bicarbonate (NaHCO3) at different concentrations (0, 4 and 8 g/L). MSE without amendment of NaHCO3, was used as negative control. The Zarrouks medium being the best medium for the growth of Spirulina as reported in the literature was used as positive control to compare the effectiveness of the MSE as a culture medium. Spirulina platensis was cultivated using MSE amended with and without NaHCO3. The cultures were analyzed for pH, protein (Bradford method), reducing sugar (DNS method), starch (Iodine method), total suspended solids (TSS) (APHA method), cell biomass by dry cell weight (DCW), and OD. The cultures were carried out during 20 days and samples were withdrawn every two days for analysis. The experiment trial was done by duplicate. The highest pH 10.52 observed was in the MSE amended with 8 g/L NaHCO3 in the first trial and 9.34 for the second. The highest DCW obtained after 20 days of cultivation observed was the Zarrouk’s medium with 1095 mg/L and in MSE with 0g/L NaHCO3 with 1445 mg/L in the first and second trial of experiments respectively. Study on effect of NaHCO3 on the glucose content of Spirulina, MSE without addition of NaHCO3 (0 g/L NaHCO3) achieved the highest glucose content with 0.35 g/L in first trial of experiment after 20th day of cultivation. It was increased by 133.33% from day 0th of cultivation with glucose content of 0.15 g/L. While, in second trial the MSE containing 4 g/L NaHCO3 was achieved the highest glucose content on the 20th day of cultivation with 0.13 g/L. An increased was shown by 44.44% from the day 0th of cultivation with glucose content of 0.09 g/L. Study on the effect of starch shows that the highest starch content for the first trial of experiment on the 20th day observed was the MSE containing 8 g/L of sodium bicarbonate, NaHCO3 with 0.21 g/L of starch content. An increased was shown by 2000% compare to day 0th of cultivation with starch content of 0.01 g/L. While, for the second trial of experiment the highest starch content was achieved in MSE without the sodium bicarbonate amendment added, 0 g/L NaHCO3 with starch content of 0.16 g/L on day 20th of cultivation. An increased was shown by 128.57% compare to day 0 of cultivation with starch content of 0.07 g/L. Study on effect of NaHCO3 of Spirulina in Zarrouk’s medium was achieved the highest protein content at 3.06% and 3.85% in first and second trials of experiments respectively. As compared to medium of MSE with different concentration of NaHCO3 amendment, the highest protein content observed was in MSE added with 8 g/L NaHCO3 with 2.31% of protein content in the first trial of experiment, while for the second trial the highest protein content was achieved by MSE without addition of NaHCO3 (0 g/L NaHCO3) with 2.92% of protein content.